Productivity enhancement of safflower (Carthamus tinctorius L.) through improved crop varieties - C. SUDHA RANI, P.SATISH, C. SUDHAKAR and (The Journal of Research, PJTSAU, 2017)
Front line demonstrations were conducted in 80 farmers fields to demonstrate production potential of and economic benefits of improved technologies comprising high yielding fusaruim and aphid resistant variety (TSF-1) in Ranga Reddy districtof Southern Telangana during rabi 2010-2011, 2011-12, 2012-13 and 2013-14 under residual soil moisture conditions The additional yield under improved technologies over local practice ranged from 221 to 279 kg/ha with a mean yield of 255 kg/ha. In comparison to local practice, there was an increase of 27% during 2010-11(TSF-1), 24% during 2011-12 (Manjira), 33% during 2012- 13(Annegeri-1) and 34% during 2013-14 (TSF-1). The improved varieties also resulted in higher benefit cost: ratio of 1.26 to 1.51 with TSF-1 compared to 0.74 to 1.09 for local check.